2015
DOI: 10.1371/journal.pone.0142123
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Effects of Polypharmacy on Clinical Outcome among Patients Aged 80+: A Five-Year Follow-Up Study

Abstract: ObjectivesPolypharmacy is a problem of growing interest in geriatrics with the increase in drug consumption in recent years, is defined according to the WHO criteria as the, ‘‘concurrent use of five or more different prescription medication”. We investigated the clinical characteristics of polypharmacy and identified the effects of polypharmacy on clinical outcome among patients aged 80+ admitted to Chinese PLA general hospital.MethodsOlder men aged ≥80 years (n = 1562) were included in this study. The include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
3
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 31 publications
(22 reference statements)
11
77
3
5
Order By: Relevance
“…Anticholinergic medications can cause peripheral (dry mouth and constipation) and central (falls, dizziness, delirium, and cognitive decline) adverse effects [26] that could participate in the development of frailty through altered nutritional intake, limitation of mobility or cognitive impairment. Gnjidic et al [27] suggested the potential contribution of medicines to the development of frailty, consistently with 14 the results of previous studies showing an increased risk of incident frailty in people with polypharmacy [9,28].…”
Section: Polypharmacy Anticholinergic Medications and Frailtysupporting
confidence: 68%
“…Anticholinergic medications can cause peripheral (dry mouth and constipation) and central (falls, dizziness, delirium, and cognitive decline) adverse effects [26] that could participate in the development of frailty through altered nutritional intake, limitation of mobility or cognitive impairment. Gnjidic et al [27] suggested the potential contribution of medicines to the development of frailty, consistently with 14 the results of previous studies showing an increased risk of incident frailty in people with polypharmacy [9,28].…”
Section: Polypharmacy Anticholinergic Medications and Frailtysupporting
confidence: 68%
“…They noted that cases with excessive polypharmacy (≥10 drugs) exhibited significantly decreased cognitive function compared to non-polypharmacy cases (0–5 drugs) [38]. However, other studies reported a lack of association between polypharmacy and cognitive impairment in men [12, 39]. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, as the definition of polypharmacy does not specify the duration of administration and the number of drugs, most commonly used criterion is the administration of five or more drugs per day for a certain period of time [712]. Polypharmacy and incidence of chronic diseases have increased concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the authors found that the risk of adverse event increased with the number of drugs taken, regardless of the type of the drug, the age of the patient or concomitant diseases. Furthermore, a 11-year follow-up performed by American researchers from 1995 to 2005 showed that in the study population the risk of iatrogenic complication was increased by 88% in patients taking 5 or more drugs and by 45% in patients taking 3 or 4 drugs when compared to those who were administered no more than two drugs [6]. What is the optimal number of drugs, which should not be exceeded?…”
Section: Limits Of Polypharmacymentioning
confidence: 97%
“…This may lead to unwanted duplication of drug, particularly since there are many generics available and a physician may prescribe a formulation containing the same active substance that the patients is already taking [6]. It is important problem, because elderly patients may have trouble understanding complicated medical recommendations or take the same drug several times a day due to memory dysfunction.…”
Section: Reasons Of Polypragmasymentioning
confidence: 99%